1988
DOI: 10.1111/j.1651-2227.1988.tb10659.x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Hyperbilirubinemia. Evidence for a Role of the Erythrocyte Enzyme Activities Involved in the Detoxification of Oxygen Radicals

Abstract: Determinations of erythrocyte enzyme scavengers of oxygen radicals (glutathione-peroxidase, superoxide-dismutase and catalase) and determinations of erythrocyte age-dependent glycolytic activities (glucose-6-phosphate-dehydrogenase, pyruvate-kinase and glucose-phosphate-isomerase) were carried out in cord blood and in the blood taken on the 4th day of life in 152 newborn infants with different peak bilirubin levels. The enzyme activities scavenging oxygen radicals, glutathione-peroxidase and superoxide-dismuta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 21 publications
0
22
0
3
Order By: Relevance
“…It has been reported in literature that jaundice produces an oxidative stress as demonstrated by decreased levels of cellular glutathione, gluthathione peroxidase and SOD in various studies (15,16). Antioxidant status in jaundiced neonates after phototherapy is not clear.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported in literature that jaundice produces an oxidative stress as demonstrated by decreased levels of cellular glutathione, gluthathione peroxidase and SOD in various studies (15,16). Antioxidant status in jaundiced neonates after phototherapy is not clear.…”
Section: Resultsmentioning
confidence: 99%
“…intermediates ( 17), and changes of RBC population ( 18) have been reported to occur shortly after birth, other factors possibly involved in the protection of the cell from oxidative hemolysis, such as the characteristics of their membrane structure, have not been fully investigated.…”
Section: Ns Nsmentioning
confidence: 99%
“…Also, in another study, authors have shown that UCB induces a dosedependent increase in neuronal death in parallel with the oxidation of cell components and a decrease in the intracellular glutathione content 4 . Bracci et al (1988) showed that antioxidant enzymes of erythrocyte were significantly lower in cord blood and on the 4th day of life in babies with high bilirubinemia compared to less jaundiced babies 48 . Recently, Dani et al (2003) have shown a decrease plasma bilirubin level and oxidative stress concominant with an increase in plasma antioxidant capacity in the preterm infants 49 .…”
mentioning
confidence: 99%